Transformative leadership: cultivating teacher excellence through satisfaction, environment, and self-efficacy - Virgana, Virgana; Fitriani, Ade (Intelektual Pustaka Media Utama, 2025)
Enhancing teacher performance (TP) in secondary education hinges on robust support in leadership, self-efficacy (SE), environment, and job satisfaction (JS). This article investigates how leadership influences TP, examining its intricate connection with JS, work environment, and SE. The study, encompassing 400 teachers, utilizes quantitative survey data subjected to exploratory factor analysis (EFA) for instruments. The data underwent path analysis employing Smart Partial Least Squares software, meeting the criterion of p0.70 for validation. Key findings demonstrate that transformational leadership, SE, and the work environment significantly influence JS. Moreover, in conjunction with JS, these factors positively impact TP. Notably, SE and an inspiring work environment indirectly enhance performance through their influence on JS. In summary, this research underscores the pivotal role of transformational leadership in TP enhancement. Transformational leaders can establish an empowering context for teachers to deliver high-quality education by prioritizing JS, the work environment, and SE. This underscores the necessity for educational institutions to emphasize administrator training in transformational leadership, thereby fostering a culture that values and supports effective leadership practices. Implications for further research suggest that transformational leadership improves TP and highlights avenues for additional exploration and application within educational contexts.